Quercetin Intake and Absolute Telomere Length in Patients with Type 2 Diabetes Mellitus: Novel Findings from a Randomized Controlled Before-and-After Study - Aikaterini E. Mantadaki; Stella Baliou; Manolis Linardakis; Elena Vakonaki; Manolis N. Tzatzarakis; Aristides Tsatsakis; Emmanouil K. Symvoulakis (MDPI AG, 2024)
Telomeres, the protective chromosomal ends, progressively shorten and potentially are implicated in the pathogenesis of age-related diseases. In type 2 diabetes (T2DM), telomere shortening may play an important role, but the whole 'picture' remains limited. From a therapeutic perspective, the phytonutrient quercetin appears to be clinically effective and safe for patients with T2DM. Considering the above, we aimed to examine whether quercetin could interfere with telomere length (TL) dynamics. One hundred patients with T2DM on non-insulin medications registered within a primary healthcare facility were stratified by age and sex and randomly assigned to either standard care or standard care plus quercetin (500 mg/day) for 12 weeks, succeeded by an 8-week washout period and another 12 weeks of supplementation. Of the 88 patients completing the trial, 82 consented to blood sampling for TL measurements. Health assessments and whole blood absolute TL measurements using quantitative polymerase chain reaction (qPCR) were conducted at baseline and study end, and the findings of this subcohort are presented. Quercetin supplementation was associated with a significant increase in mean TL (odds ratio ≥ 2.44; p < 0.05) with a strengthened association after full adjustment for potential confounders through multiple logistic regression analysis (odds ratio = 3.48; p = 0.026), suggesting it as a potentially promising supplementation option. Further studies are needed to confirm this finding, elucidating the underlying molecular mechanisms of quercetin.